Laparoscopic Single Site Surgery for Repair of Retrocaval Ureter in a Morbidly Obese Patient - Aly M. Abdel-Karim; Elsayed Yahia; M. Hassouna; Mostafa M. Elmissiry (Urology Case Reports, 2016)
This is to describe a case of a morbidly obese (BMI = 40) female with retrocaval ureter treated with laparoendoscopic single-site surgery. A JJ stent was positioned. A 2 cm umbilical access was created. A single port platform was positioned. The entire ureter was mobilized posterior to the vena cava and transected where the dilated portion ended. The distal ureter was repositioned lateral to the inferior vena cava. Anastomosis was done. A 3 mm trocar was used to assist suturing. At 4-month follow-up, CT revealed no evidence of obstruction of the right kidney and the patient was symptomless. Although challenging, in a morbidly obese patient, LESS repair for retrocaval ureter is feasible.